Influence of Collection Areas on the Physico-chemical and Nutritional Characterization of Dried Mangoes Consumed in Chad for Better Post-Harvest Valorization - Mahamat, Al-Lamadine; Ousman, Abdoullahi Hissein; Nazal, Alhadj Markhous; Ahmat, Brahim Adoum; Haroune, Ali; Valery, Mbaigolmem Beral; Tapsoba, François; Leonce, Azabadji Ashu Evariste; Issakou, Bakaranga Via; Tidjani, Abdelsalam (Current Perspectives in Agriculture and Food Science Vol. 9, 2024)
Background: Mango plays a very important nutritional role, providing micronutrients required for the proper functioning of the human body and protection against major chronic diseases such as cardiovascular, neurodegenerative and metabolic diseases, as well as cancers. Aim: This study aims to determine the chemical and nutritional characterization of dried mangoes consumed in Chad for better post-harvest valorization. Methodology: The study was conducted in the Food Sciences and Nutrition Research Laboratory (LARSAN), Faculty of Human Health Sciences, University of N’Djamena BP1117, Chad; between February 2022 and April 2023. Dried mangoes were collected from five localities (Doba, Bebedjia, Koumra, Moundou, and Bongor), were labeled DbaA, Bja, Mdou, Kmr, and Bgr, and then stored in a refrigerated cooler for physico-chemical analyses using standard methods to determine the chemical composition of various samples. The statistical analysis was carried out using the ANOVA test (analysis of variance test) followed by the Fisher post hoc test to compare means. Results: These analyses showed that the water content of dried mangoes was not significantly influenced (p = 0.0014) by the production area. No significant difference (P>0.05) was observed in the Vitamin composition of dried mangoes from the five locations. Protein, carbohydrate, lipid, and energy contents per 100 g ranged from 3.89 to 3.93 g, 94.91 to 104.72 g, 1.35 to 2.07 g, and 360.48 to 381.36 kcal/100 g, respectively. The reducing sugar content was high (77.73 g/100g) in Doba samples, compared to that from Moundou (76.51 g/100g). Starch and amylopectin contents were not significantly affected by production area (110.32 to 112.07 g/100g and 94.28 to 97.20 g/100 g, respectively). Calcium (Ca), sodium (Na), potassium (K), magnesium (Mg), and iron (Fe) were present in all samples with respective contents varying from 72.66 to 73.49 mg/100 g, 11.41 to 12.58 mg/100 g, 79.15 to 85.97, 68.78 to 70.59 mg/100 g, and 1.05 to 1.79 mg/100 g. Vitamin C and carotenoid contents varied, respectively, from 69.37 to 70.15 \(μ\)g/100 g and from 249.25 to 274.15 \(μ\)g/100 g. Principal Component Analysis revealed that samples E1DOBA and E2BGA and E3Kmr and E4Mdr have the same physico-chemical characteristics. Conclusion: These findings revealed that dried fruits from all localities were kept well, as their water content fell within the norm. Thus, these results demonstrate that respecting the drying and storage conditions for dried mango fruits, regardless of the zone, would enable the best possible preservation of nutritional properties while ensuring year-round availability.